Stability of O/W Emulsion with Synthetic Perfumes Oxidized by Singlet Oxygen. (5th March 2013) - Watabe, Naoki; Tokuoka, Yoshikazu; Kawashima, Norimichi
Abstract : We prepared O/W emulsion composed of a synthetic perfume, n -dodecane, protoporphyrin IX disodium salt (PpIX-2Na), sodium dodecyl sulfate, and water and investigated oxidative decomposition of the synthetic perfume in the emulsion and change in the stability of the emulsion by singlet oxygen ( 1 O2 ) generated by photosensitization of PpIX-2Na. We used eugenol, linalool, benzyl acetate, α -ionone, α -hexylcinnamaldehyde, and d -limonene as a synthetic perfume. The stability of the O/W emulation including eugenol and linalool significantly decreased with increasing light irradiation time. The decrease in the emulsion stability may be attributable to oxidative decomposition of eugenol and linalool by 1 O2 and enlargement of the oil droplet size.